Post COVID-19 Pandemic International Travel: Does Risk Perception and Stress-Level Affect Future Travel Intention? - Ahmad Febri Falahuddin; Clare Teroviel Tergu; Rachele Brollo; Ratih Oktri Nanda (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
The COVID-19 pandemic has extremely affected several industries including international travel and tourism. Many scholars have tried to describe the cause-effects of this major phenomenon. This study majorly aims to explore the relationship between risk perception and travel intention where stress level prone to COVID-19 quarantine serves as a moderating factor. The researchers believed that the influence of the dimensions of risk perception including social risk, psychological risk, physical risk, performance risk, financial risk and time risk on travel intention will be significant when the variable of stress level intervenes. This paper used a quantitative approach involving 409 respondents around the world. The data were gathered via online questionnaires facilitated by Google form and Wenjuanxing. The respective questionnaires were available in five languages (Chinese, English, Italian, French and Indonesian). Both descriptive and inferential statistics were used to analyze the data. The outcome of the hierarchical multiple regression (HMR) test resulted in a positive connection between all independent variables and travel intention simultaneously but not partially. The uppermost influence was found in social risk. Meanwhile, financial risk and time risk indicate no significant relationship. Lastly, the researchers believe that understanding the relationships between the variables of this study would be beneficial for the DMOs to predict the future market and rearrange strategies after being affected by the pandemic.